Chemically Reactive Thin Films: Dynamics and Stability - Richter, Tilman; Malgaretti, Paolo; Koller, Thomas Manfred; Harting, Jens (Advanced Materials Interfaces, 2025)
Catalyst particles or complexes suspended in liquid films can trigger chemical reactions leading to inhomogeneous concentrations of reactants and products in the film. It is demonstrated that the sensitivity of the liquid film's gas–liquid surface tension to these inhomogeneous concentrations strongly impacts the film stability. Using linear stability analysis, novel scenarios are identified in which the film can be either stabilized or destabilized by the reactions. Furthermore, it is found so far unrevealed rupture mechanisms which are absent in the chemically inactive case. The linear stability predictions are confirmed by numerical simulations, which also demonstrate that the shape of chemically active droplets can depart from the spherical cap and that unsteady states such as traveling and standing waves might appear. Finally, critically discussed the relevance of the predictions by showing that the range of the selected parameters is well accessible by typical experiment